(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
This article examines the significance of developing manual skills in preschool education, emphasizing their role in cognitive, social, emotional, and neuropsychological development. Manual activities strengthen fine motor coordination, promote creativity, support sensory integration, and build foundational competencies required for early literacy and daily problem-solving. The paper presents a scientific analysis of the mechanisms that underlie manual skill formation and highlights pedagogical strategies that effectively support young children’s hands-on learning.